The Study Of Erosion Level Based Of Usage Landcliff Of Head Water In Batang Lumpo Flow Rod District IV Jurai Sub-Province Pesisir Selatan - Satrianto, Febri; Edial, MT, Drs. Helfia; Thesiwati, SP., M.Si, Aslan Sari (STKIP PGRI Sumbar, 2014)
ABSTRACT This study aimed to determine the rate of erosion Based On The cliffs of Land Use in the Upper River Flows Rod Part Lumpo District of South Coastal District IV Jurai.The method used in this research is descriptive method, sampling method in this study is purposive sampling method (Choosing Samples), where the unit of measurement is the headwaters of Batang Lumpo .Measured erosion rates based on land use, vegetation type, slope climbing, and distribution of rocks. The results showed that: (1) The rate of erosion in the study area based on land use categories have easily eroded, (2) The rate of erosion in the study area based on vegetation classified as a category that is easy to erosion, making it susceptible to erosion. Types of vegetation consisting of grass, paddy fields, coconut, areca nut, mango, banana, chocolate and durian. This situation makes the vegetation upstream Trunk Lumpo relatively easily eroded , ( 3 ) The rate of erosion in the study area belong to the category of rock slope based on the skew between 14-21 % . This slope causes the potential to moderate erosion on the upstream rod Lumpo and (4) The rate of erosion in the study area based distribution of rocks on the upstream rod Lumpo classified as moderate because it consists of gravel and sand.